Women's experiences on the use of Implanon as a contraceptive method in a selected primary healthcare facility in KwaZulu-Natal - Lucky N. Mgobhozi; Pretty N. Mbeje; Gugu G. Mchunu (AOSIS, 2021)
Background: The South African department of health recently introduced subdermal Implanon contraceptive implant with the aim to reduce teenage pregnancy and maternal mortality. First used in all public healthcare facilities across the country since early 2014, this method of contraception has been described as highly effective. However, some women have reported unbearable side effects, forcing them to remove the contraceptive implant early before its expiry date. Negligible emphasis has been placed on staff training and development to equip the nurses with new protocol and policies on Implanon. Objectives: The objective of this study was to explore experiences of women using Implanon as method of contraception at a selected primary healthcare facility in KwaZulu-Natal province of South Africa. Methods: A qualitative, descriptive and exploratory study design was used. A purposive sampling technique was used and a sample of seven women aged between 15 and 50 years was selected for this study. Semi-structured interviews were used in the data collection process. The Tesch's method for data coding and data analysis was utilised. Necessary ethical measures were taken to ensure that the study is trustworthy. The study was conducted at Community Health Centre, KwaZulu-Natal between June 2017 and December 2018. Results: The findings showed that some participants were still willing to continue using this method of contraception regardless of the unwanted side effects. Major side effects reported were heavy menstrual bleeding, pain and discomfort, weight loss, insomnia and decreased sexual interest, which resulted in most participants stopping the use of Implanon. Conclusion: Most of the participants' experience unwanted side effects because of poor screening, counselling and support. There is a clear demand to develop a screening tool and facilitate training of healthcare workers when initiating the use of Implanon.